Human oral isolate Lactobacillus fermentum AGR1487 induces a proinflammatory response in germ-free rat colons - Anderson, R.; Ulluwishewa, Dulantha; Young, W.; Ryan, L.; Henderson, G.; Meijerink, M.; Maier, E.; Wells, J.; Roy, N. (Nature Publishing Group, 2016)
Lactobacilli are thought to be beneficial for human health, with lactobacilli-associated infections being confined to immune-compromised individuals. However, Lactobacillus fermentum AGR1487 negatively affects barrier integrity in vitro so we hypothesized that it caused a pro-inflammatory response in the host. We compared germ-free rats inoculated with AGR1487 to those inoculated with another L. fermentum strain, AGR1485, which does not affect in vitro barrier integrity. We showed that rats inoculated with AGR1487 had more inflammatory cells in their colon, higher levels of inflammatory biomarkers, and increased colonic gene expression of pro-inflammatory pathways. In addition, our in vitro studies showed that AGR1487 had a greater capacity to activate TLR signaling and induce pro-inflammatory cytokines in immune cells. This study indicates the potential of strains of the same species to differentially elicit inflammatory responses in the host and highlights the importance of strain characterization in probiotic approaches to treat inflammatory disorders.